2021
DOI: 10.3390/ijms222011171
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Lactiplantibacillus plantarum IMC 510 Modifies Microbiota Composition and Prevents Body Weight Gain Induced by Cafeteria Diet in Rats

Abstract: Changes in functionality and composition of gut microbiota (GM) have been associated and may contribute to the development and maintenance of obesity and related diseases. The aim of our study was to investigate for the first time the impact of Lactiplantibacillus (L.) plantarum IMC 510 in a rat model of diet-induced obesity, specifically in the cafeteria (CAF) diet. This diet provides a strong motivation to voluntary overeat, due to the palatability and variety of selected energy-dense foods. The oral adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 115 publications
(141 reference statements)
2
13
0
Order By: Relevance
“…Oral intake of probiotic preparations of the strains Lactobacillus casei and Bifidobacterium bifidum (alone or both simultaneously) reduced the incidence of hyperglycaemia (increased blood glucose concentration) and dyslipidaemia (imbalance of blood lipid concentration) in rats with induced diabetes [ 79 ]. Similar antidiabetic effects in rats were obtained by administration of probiotic strains Lactobacillus plantarum TN627 [ 80 ], Bifidobacterium animalis 01 [ 81 ], Lactobacillus paracasei HII01 [ 82 ], 9 strains of Lactobacillus rhamnosus , Bifidobacterium adolescentis and Bifidobacterium bifidum [ 77 ], Lactobacillus rhamnosus BSL and R23 [ 83 ], heat-inactivated Streptococcus thermophilus [ 84 ], Lactiplantibacillus plantarum IMC 510 [ 85 ] and Lactobacillus fermentum RS-2 [ 86 ]. In the latter case, in addition to reduced glucose levels in fasting state, a low oxidative stress was observed [ 86 ].…”
Section: Effect Of Probiotics On Glucose Metabolism and Homeostasismentioning
confidence: 88%
“…Oral intake of probiotic preparations of the strains Lactobacillus casei and Bifidobacterium bifidum (alone or both simultaneously) reduced the incidence of hyperglycaemia (increased blood glucose concentration) and dyslipidaemia (imbalance of blood lipid concentration) in rats with induced diabetes [ 79 ]. Similar antidiabetic effects in rats were obtained by administration of probiotic strains Lactobacillus plantarum TN627 [ 80 ], Bifidobacterium animalis 01 [ 81 ], Lactobacillus paracasei HII01 [ 82 ], 9 strains of Lactobacillus rhamnosus , Bifidobacterium adolescentis and Bifidobacterium bifidum [ 77 ], Lactobacillus rhamnosus BSL and R23 [ 83 ], heat-inactivated Streptococcus thermophilus [ 84 ], Lactiplantibacillus plantarum IMC 510 [ 85 ] and Lactobacillus fermentum RS-2 [ 86 ]. In the latter case, in addition to reduced glucose levels in fasting state, a low oxidative stress was observed [ 86 ].…”
Section: Effect Of Probiotics On Glucose Metabolism and Homeostasismentioning
confidence: 88%
“…Each capsule contained 1.5 × 10 10 bacterial cells of the human origin strain Lact. plantarum IMC 510, isolated and characterized by Synbiotec S.r.l., and deposited at the Deutsche Sammlung von Mikroorganismen und Zelkulturen (DSMZ) collection with the identification number DSM 32548 (Coman et al, 2021;Coman & Cresci, 2014;Silvi et al, 2003). Compared with the probiotic capsules, the placebo ones contained just the same carrier material and were similar in size, shape and taste.…”
Section: Probiotic Strain Supplementationmentioning
confidence: 99%
“…The potential probiotic strain Lactiplantibacillus plantarum IMC 510, tested in the present pilot clinical trial, was previously isolated from healthy human subjects, identified by 16S rRNA gene sequence analysis, characterized as probiotic strain and tested for safety (resistance to low pH, bile salts and pancreatic juice, ability to adhere to intestinal cells and colonize the mucosa, antipathogenic activity against gram-positive and gram-negative bacteria and yeasts, non-transmissible antibiotic resistance genes', absence of plasmids) by Synbiotec S.r.l. (Coman et al, 2021;Coman & Cresci, 2014;Silvi et al, 2003). Furthermore, Lact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactiplantibacillus plantarum IMC 509 is a further strain isolated by Synbiotec S.r.l. from the intestinal tract of elderly humans and is well characterized for its probiotic traits [ 15 , 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%